Constitutional Justice in Latin America - Landa Arroyo, César (2014)
From the relationship between Democracy and Constitutionalism in Latin America, the author addresses the issue of constitutional justice as an entity of control of the constitutionality of the laws, which would have power against majority when it derogates an unconstitutional legislation. Also, the author reflects on the protection of fundamental rights in the region, analyzing the nuances presented in terms of the various constitutional conceptions.